1996
DOI: 10.1016/s0893-133x(96)00090-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Side-Effects of Clozapine: Testing for Association with Allelic Variation in the Dopamine D4 Receptor Gene

Abstract: Genetic factors are supposed to play a major role not only in the etiology of psychiatric disorders but also in individual response to medications. To test the hypothesis that inter-individual differences in response to clozapine and the occurrence of side-effects might be influenced by variations in the dopamine D4 receptor gene, we examined frequencies of four known polymorphic sites affecting protein structure in the dopamine D4 receptor gene in 149 patients with schizophrenia or schizoaffective disorder tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 22 publications
1
33
0
2
Order By: Relevance
“…We therefore studied the population frequencies of the 48-bp repeat region in a large Caucasian population composed of schizophrenic patients, healthy subjects, and non-psychiatric patients. In accordance with the observations of Asghari et al, 8,9 van Tol et al, 7 and Cohen et al, 11 we grouped all individuals carrying DRD4 48-bp VNTR genotypes with Յ 4-repeat alleles (genotypes: 14,22,23,24,33,34,44) and Ն 5-repeat alleles (all other genotypes as shown in Table 1), and all individuals carrying only Յ 4-repeat alleles with Ն 5-repeat alleles. We were primarily interested in the relation between therapeutic response and the 48-bp VNTR in patients treated with clozapine, as well as in patients treated with typical antipsychotics.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…We therefore studied the population frequencies of the 48-bp repeat region in a large Caucasian population composed of schizophrenic patients, healthy subjects, and non-psychiatric patients. In accordance with the observations of Asghari et al, 8,9 van Tol et al, 7 and Cohen et al, 11 we grouped all individuals carrying DRD4 48-bp VNTR genotypes with Յ 4-repeat alleles (genotypes: 14,22,23,24,33,34,44) and Ն 5-repeat alleles (all other genotypes as shown in Table 1), and all individuals carrying only Յ 4-repeat alleles with Ն 5-repeat alleles. We were primarily interested in the relation between therapeutic response and the 48-bp VNTR in patients treated with clozapine, as well as in patients treated with typical antipsychotics.…”
Section: Introductionsupporting
confidence: 54%
“…9 A number of clinical studies 10,11 have confirmed, and others have denied, the association between different alleles of the 48-bp repeat and the response to antipsy-chotic drug treatment. [12][13][14] The DRD4 receptor has also been investigated for possible linkage to schizophrenia, since DRD4 density was found in post-mortem brain tissues of schizophrenic patients 15 which was six times greater than that among non-psychiatric controls. Most studies investigating schizophrenia have not been able to find significant association of the DRD4 48-bp VNTR.…”
Section: Introductionmentioning
confidence: 99%
“…38 Of note also is the widespread distribution of d4 mRNA, a high affinity site for clozapine, 39 although no association between the polymorphic forms of d4 or variable clozapine response has been found. 40,41 The mapping of serotonin receptors in peripheral blood cells indicated variable levels of expression, with 5ht7 mRNA most widely distributed and 5ht2c and 5ht6 mRNA undetected. Serotonin-mediated regulation of hematopoiesis via programmed cell death has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Three independent studies failed to confirm these associations. [108][109][110] Studies of genetic variants in the dopamine transporter gene (DAT1) reported several associations between a VNTR polymorphism and response to methylphenidate, a treatment for attention deficit and hyperactivity disorder (ADHD), 163,164 but no association has been reported with antipsychotic response. 102,103,111 The final reading of these association findings is that they confirm the contribution of dopamine receptors to antipsychotic efficacy.…”
Section: Pharmacodynamic Factorsmentioning
confidence: 99%